SOSIALISASI TENTANG KONSEP DASAR PAUD BAGI GURU, ORANGTUA, DAN MASYARAKAT DI KECAMATAN REOK - Maria Fatima Mardina Angkur (Unika Santu Paulus Ruteng, 2022)
Early childhood education is an educational service aimed at children from birth to the age of 6 years. In order to run the education well, of course, there are many parties involved. These include parents, teachers, and the community. Parents, teachers, and the community have a very important role in early childhood education. The fact found in the field is that there are still differences in the concept of early childhood education between parents, teachers, and the community. Seeing this reality, it is very necessary to hold outreach activities related to the Basic Concept of PAUD for parents, teachers, and the community in Reok District. The material presented is material related to the Nature of PAUD, the Foundation for the Implementation of PAUD, the Principles of Early Childhood Education, the Competence of PAUD Teachers, the Role of PAUD Teachers, and the Role of Parents in PAUD. The hope to be achieved from this activity is the harmony or similarity of the basic concepts of PAUD